America betrayed [videorecording (DVD)] : how government and big business bring ruin to America's infrastructure - Cardé, Leslie; Dreyfuss, Richard (First Run Features, 2009)
America's infrastructure was once our proudest achievement. Now its a most dangerous embarrassment. Bridges, dams, levees and highways are crumbling, toppling, being washed away, and putting us all at risk. Features interviews with journalists, noted scientists, whistleblowers who risked their lives to speak out, and politicians from both sides. Exposes the rampant collusion, corruption and cronyism within the government agencies whose very purpose is to protect us.